The role of weed control in integrated pest management for tropical root and tuber crops - Akobundu, I.O. (1990)
A discussion is given of control of weeds of root and tuber crops, such as cassava, sweet potatoes, yams and cocoyams [Colocasia esculenta], as part of an integrated pest management programme.